2003
DOI: 10.1046/j.1365-2516.2003.00782.x
|View full text |Cite
|
Sign up to set email alerts
|

Control of bleeding in patients with haemophilia A with inhibitors: a systematic review

Abstract: This paper reports a systematic review of the best available evidence of clinical effectiveness in the treatment of acute bleeding in haemophilia A patients with inhibitors. Because of the lack of randomized controlled trials (RCTs) on this topic, broad inclusion criteria with regard to study design were applied in order to assess the best available evidence for each intervention. Because of the clinical and methodological heterogeneity of the evidence, it was not appropriate to pool data across studies; inste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 71 publications
(216 reference statements)
0
47
0
Order By: Relevance
“…The efficacy of any bypassing agent varies, as seen in many studies; factor eight inhibitor bypassing activity (FEIBA) is effective in 80-100% of cases (6). On the other hand, other studies have reported more than 90% success, which was close to 60% when rFVIIa was used in treating acute bleeds (7). However, these studies demonstrate that bypassing agents are effective in most cases, although none of them is universally effective (6).…”
Section: Contextmentioning
confidence: 76%
“…The efficacy of any bypassing agent varies, as seen in many studies; factor eight inhibitor bypassing activity (FEIBA) is effective in 80-100% of cases (6). On the other hand, other studies have reported more than 90% success, which was close to 60% when rFVIIa was used in treating acute bleeds (7). However, these studies demonstrate that bypassing agents are effective in most cases, although none of them is universally effective (6).…”
Section: Contextmentioning
confidence: 76%
“…Pd-aPCC is effective in controlling hemorrhage at a variety of anatomic sites including joint, muscle, mucocutaneous, and central nervous system (CNS) and perioperative bleeding,1719 and can also be used effectively to achieve hemostasis in a home-treatment setting 14. Mild adverse events, such as chills, fever, nausea, and dizziness, occur in a small proportion of patients,20 and there is a small risk of anaphylactic reactions 21. Thrombotic and thromboembolic events (including disseminated intravascular coagulation [DIC], venous thrombosis, pulmonary embolism, myocardial infarction, and stroke) have been reported following infusion of pd-aPCC 21.…”
Section: Bypassing Therapy For Patients With Inhibitorsmentioning
confidence: 99%
“…In addition, pd-aPCC contains trace amounts of factor VIII that may induce an anamnestic rise in factor VIII antibody titers in up to 30% of patients 19,21. This rise in antibody titers does not interfere with the efficacy of pd-aPCC and is transient in the majority of patients 20. Despite these limitations, this product has been widely used for about 30 years and continues to be used in patients who may not respond to rFVIIa.…”
Section: Bypassing Therapy For Patients With Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bleeding episodes are effectively treated by replacing the deficient factor; however, it is common for patients to develop inhibitors to factor VIII or IX, which leads to severe and expensive complications from treatment [2, 3]. The presence of high titer inhibitors, in particular, renders replacement therapy completely ineffective.…”
Section: Introductionmentioning
confidence: 99%